PROFESIONALISME GURU DI WILAYAH PERBATASAN INDONESIA: ANALISIS TANTANGAN, STRATEGI, DAN KEBIJAKAN PENDIDIKAN - Khairuddin, M.; Akwila, Akwila; Widka, Agustina; Cahyadi, M.F.; Arisdiyoto, Iving (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
This study examines the issue of teacher professionalism in Indonesia’s border areas, which still face significant disparities compared to urban regions. Using a qualitative approach through library research, this article analyzes the current conditions, challenges, and strategies for strengthening teacher professionalism in 3T areas (frontier, outermost, disadvantaged regions). The findings indicate that teachers in border areas encounter structural, geographical, socio-cultural, and psychosocial barriers, ranging from unequal teacher distribution, limited incentives, inadequate school facilities, to weak community support. Government programs such as SM-3T, Frontline Teacher (GGD), and the National Teacher Distribution System (SPGN) have been implemented, yet their effectiveness remains limited. Non-governmental initiatives and educational technology innovations present opportunities, but digital infrastructure and literacy gaps remain major challenges. This study highlights the need to strengthen teacher professionalism through a holistic approach that integrates government policies, local community participation, philanthropic support, and contextualized digital innovations. Such an approach is essential not only for improving educational quality and equity but also for reinforcing national resilience in border regions.